Reviving the glory of healthcare waqf / Sulistyowati - -, Sulistyowati (UiTM Cawangan Johor, 2019)
Referring to (Baqutayan, 2018) and (Atan, et al., 2017) as main references, this article aims to Evaluate the success of recent healthcare waqf; Synthesize the previous studies of healthcare waqf in order to strengthen the thought; Identify Bimaristans as kind of success healthcare waqf in the past and Analyze the possibility of reviving the glory of healthcare waqf. This study adopts an in-depth interview to collect primary data and content analysis as secondary data based on many articles. Result shows that First, the evaluation of the recent healthcare waqf practices shows that there are significant development of several OIC countries such as Malaysia, Indonesia, and Turkey, However for other countries such as Uganda, Bangladesh, and Pakistan needs serious attention to revive the success of healthcare waqf; Second, the previous related literature study synthesized that there were fewer articles focuses on empirical evidence of waqf healthcare compared to many recent waqf-based healthcare practices in the world; Third, the identification of historical study recapitulates that the excellence of Bimaristan in the form of high healthcare and treatment standard was still better compared to the standard quality of current hospital; and Fourth, reviving the glory of healthcare waqf is possible by realizing waqf-based integrated-modern healthcare services which are all parties both government and private stakeholders collaborate in beautiful cooperation. For future study, the author recommends that topic should be deepened in the direction of more practical empirical research in order to find the most suitable model and brings it into practice according to waqf-based healthcare sufficiency for the poor.